2017
DOI: 10.3122/jabfm.2017.01.160183
|View full text |Cite
|
Sign up to set email alerts
|

Primary Care Clinic Re-Design for Prescription Opioid Management

Abstract: Background:The challenge of responding to prescription opioid overuse within the United States has fallen disproportionately on the primary care clinic setting. Here we describe a framework comprised of 6 Building Blocks to guide efforts within this setting to address the use of opioids for chronic pain.Methods: Investigators conducted site visits to thirty primary care clinics across the United States selected for their use of team-based workforce innovations. Site visits included interviews with leadership, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
21
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(22 citation statements)
references
References 13 publications
1
21
0
Order By: Relevance
“…34–36 Furthermore, the TOPCARE intervention shares characteristics of opioid-prescribing practices among 30 primary care clinics noted nationally for practice innovations 37 : leadership support through clinical champions, revision of prescribing workflows, population management through a registry, planned patient-centered visits (with the nurse care manager), and assessment of progress via data. Nurse care managers play key roles in coordinating the intervention, such as ensuring that monitoring (ie, UDT, pill counts) occurred, interfacing with patients and PCCs to resolve concerning behaviors or pain-relatedneeds, managing the registry (inputting data, printing reports for academic detailing) and directing patients and PCCs to the TOPCARE website (http://mytopcare.org/).…”
Section: Discussionmentioning
confidence: 99%
“…34–36 Furthermore, the TOPCARE intervention shares characteristics of opioid-prescribing practices among 30 primary care clinics noted nationally for practice innovations 37 : leadership support through clinical champions, revision of prescribing workflows, population management through a registry, planned patient-centered visits (with the nurse care manager), and assessment of progress via data. Nurse care managers play key roles in coordinating the intervention, such as ensuring that monitoring (ie, UDT, pill counts) occurred, interfacing with patients and PCCs to resolve concerning behaviors or pain-relatedneeds, managing the registry (inputting data, printing reports for academic detailing) and directing patients and PCCs to the TOPCARE website (http://mytopcare.org/).…”
Section: Discussionmentioning
confidence: 99%
“…Future research should also further explore community partnerships and primary care as an effective distribution hub for naloxone, which is an antidote that can reverse opioid overdoses if administered in time . Finally, safe prescribing of opioids is essential to preventing opioid use disorder, and future research should focus on training providers to prescribe responsibly …”
Section: Discussionmentioning
confidence: 99%
“…51,52 Finally, safe prescribing of opioids is essential to preventing opioid use disorder, and future research should focus on training providers to prescribe responsibly. 53,54 Improving access to treatment for substance use disorders in primary care is a critical part of the strategy to combat the opioid use disorder epidemic. The primary care setting offers a unique opportunity to educate, engage, and motivate patients to initiate and sustain substance use disorder treatment.…”
Section: Discussionmentioning
confidence: 99%
“…In an effort to identify common attributes of clinic system changes around managing chronic opioid therapy, Parchman et al 8 conducted site visits at 20 primary care clinics nationwide, which were selected for their use of team-based workforce innovations. A common set of 6 best practices were identified that address complex challenges of managing chronic opioid therapy in primary care settings.…”
Section: Integrated Carementioning
confidence: 99%